2019
DOI: 10.1002/jcb.28267
|View full text |Cite
|
Sign up to set email alerts
|

Analysis of synonymous codon usage pattern of genes in unique non–blood‐sucking leech Whitmania pigra

Abstract: Whitmania pigra is a unique, fluid-sucking ectoparasite and an anticoagulant medical leech. The codon usage bias (CUB) is the nonuniform usage of synonymous codons in which some codons are more preferred than others. Here, we performed a comprehensive analysis of CUB of genes in W. pigra, analyzing 140 780 transcripts, 59 553 unigenes, and 20 304 qualified coding sequences (CDSs) from the transcriptomic data of W. pigra. The effective number of codons values suggested that the CUB was low in these genes. We re… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
2
1

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 30 publications
0
3
0
Order By: Relevance
“…The ’mutation-selection drift’ theory has been employed to depict the origin of codon usage bias (CUB) of a gene [ 55 , 56 ]. The theory explains that evolutionary forces such as the selection of compositional constraints, mutation pressure, along with genetic drift in a population might play an effective role in the usage of codon bias [ 57 ]. Earlier studies have reported that genes within a species exhibit similar patterns of codon usage [ 58 , 59 ].…”
Section: Discussionmentioning
confidence: 99%
“…The ’mutation-selection drift’ theory has been employed to depict the origin of codon usage bias (CUB) of a gene [ 55 , 56 ]. The theory explains that evolutionary forces such as the selection of compositional constraints, mutation pressure, along with genetic drift in a population might play an effective role in the usage of codon bias [ 57 ]. Earlier studies have reported that genes within a species exhibit similar patterns of codon usage [ 58 , 59 ].…”
Section: Discussionmentioning
confidence: 99%
“…Whitmania pigra , as a nonblood‐feeding species, is the most commonly available leech from the traditional Chinese medicine market, which mainly relies on artificial farming (Luo et al, 2019 ; Lynn, 2019 ). Currently, W. pigra is being threatened by several diseases during farming, including edema disease, white spot disease, and withered disease, which have cumulatively caused a devastating drop (70%) in W. pigra production (Wei et al, 2018 ).…”
Section: Introductionmentioning
confidence: 99%
“…Reports suggest that W. pigra is microphagous, non-blood-sucking and mostly prey on eld snails (Weisblat, 2003;Kuo and Lai, 2019). Although it exhibits nonblood feeding character, many researchers have identi ed anticoagulation peptides from this leech and located the molecular basis to the synthesis of such substances (Chu et al, 2016;Khan et al, 2019a;Khan et al, 2019b;Hu et al, 2020;Huang et al, 2020). Phylogenetically, W. pigra belongs to the family Hirudinidae.…”
Section: Introductionmentioning
confidence: 99%